The Effect of Pacemakers and Defibrillators on Distortion in 2 Magnetic Resonance Imaging (MRI) Sequences Commonly Used in Radiation Oncology Practice—3D True Fast Imaging with Steady State Precession (TrueFISP) at 0.35T MR-Linear Accelerator (LINAC) and 3D T1 at 3T MR Simulator - Alireza Omidi; Elisabeth Weiss; Mateb Al Khalifa; Siyong Kim (Radiation)
Background: We aimed to measure the pacemaker- and defibrillator-induced distortion at 0.35T and 3.0T magnetic fields. Methods: The pacemaker/defibrillator was placed at the top center of a water-filled/MagPhan phantom, followed by a T1 scan at 3T and a TrueFISP scan at 0.35T. The extent of distortion (i.e., the distance from the device to the furthest signal loss/void/rings) in the water-filled phantom was measured in MIM. For geometrical distortion (i.e., dislocation of geometrical structures), the spheres in the MagPhan phantom were contoured and their distortion was calculated based on their manufacturing coordinate positions. Results: The maximum extent of distortion caused by the defibrillator was 18.8 cm at 0.35T and 5.8 cm at 3.0T. Similarly, the maximum extent of distortion caused by the pacemaker was 9.28 cm at 0.35T and 2.8 cm at 3.0T. Geometrical distortion measurements using the MagPhan phantom showed that the maximum distortion caused by the defibrillator was 12.8 mm at 0.35T and 13.2 mm at 3.0T. Likewise, the maximum distortion caused by the pacemaker was 8.7 mm at 0.35T and 6.0 mm at 3.0T. Conclusions: Defibrillators cause larger distortions/signal voids than pacemakers, and require careful consideration when performing MRI-based treatment planning. To minimize distortion, sequences with lower sensitivity to magnetic field inhomogeneity should be used.